Book Review: McCranie, J.R., L.D. Wilson - G. Köhler. 2005. Amphibians and Reptiles of the Bay Islands and Cayos Cochinos, Honduras - Sasa, Mahmood (2007)
During the last four years, we have witnessed the publication of several important books that summarized current knowledge on the herpetofauna of Central America: Savage's (2002) The Amphibians and Reptiles of Costa Rica, McCranie and Wilson's (2002) The Amphibians of Honduras, Campbell and Lamar's (2004) The Venomous Reptiles of the Western Hemisphere, and Solórzano's (2004) Serpientes de Costa Rica. Recently, McCranie, Wilson and Köhler inspire us with a volume on the species of amphibians and reptiles that inhabit the department of Islas de la Bahia, in the Caribbean sea of Honduras.